'Sweet talk': framing the merits of a sugar tax in Australia. (26th January 2021) - Anaf, Julia; Fisher, Matthew; Handsley, Elizabeth; Baum, Fran; Friel, Sharon
Summary: Although rising rates of obesity are recognized as a major concern for Australian public health, debate on what (if any) responsive action should be undertaken is conceptually and normatively complex. It is shaped by diverse values and interests; different representations of the problem; and many options for action by government, the private sector or individuals. This paper presents research documenting arguments for and against implementing a sugar tax in Australia. It is based on semi-structured interviews with representatives from industry ( n = 4), public health ( n = 4), policy think tanks ( n = 2); and document and media analyses. The research design was informed by framing and agenda setting theory with results reported under four main themes: framing economic impacts, framing equity, framing obesity and framing the 'nanny state' versus individual liberty argument. We found that proposals for a sugar tax as part of policy responses to the issue of overweight and obesity in Australia are framed very differently by actors who either support or oppose it. A conclusion is that policy makers and public health advocates involved in policy debates on a sugar tax need to understand the role of problem and 'solution' framing, and develop positions based on protecting the public interest as a basic ethical responsibility of governments and public agencies.